Influence of forest Covers on Physico-chemical And Site Characteristics in Doon Valley - Narain, Pratap; Singh, Ravender; Singh, Kalyan (Indian Forester, 1990)
Studies were conducted on soil nutrient status, their dynamics and physico-chemical characteristics of soil under Sal. Eucalyptus and Brushwood forests in Doon valley. Annual return of nutrients through leaf fall was maximum under Sal forest followed by Brushwood and Eucalyptus. The understorey biomass and nutrients contained therein were however bighest in Eucalyptus followed by Brushwood and Sal forest. Organic carbon, total nitrogen, available rotash and exchangeable calcium and magnesium in soil were maximum in Brushwood forest allowed by Eucalyptus and Sal but available phosphorus was more under Sal. Accumulation of nutrients was conspicuous in surface soil while lower depths (90-210 cm) did not show much hange in nutrient status. The 0-10 cm layer was the richest in respect to all the nutrients due to their recycling through leaf-fall or understorey. Site quality was estimated to be II under Eucalyptus and Sal forests. Soil bulk density increased and correspondingly porespace percentage decreased with increasing soil depth. Lower bulk density and higher porespace percentage was found under Brushwood forest, followed by Eucalyptus and then Sal forests. Soil moisture retention curves showed higher water retention and available water under Brushwood followed by Eucalyptus and then Sal. Infiltration rates and cumulative infiltration rates were also higher under Brushwood followed by Eucalyptus and then Sal. These physical characteristics are due to higher organic carbon content in Brushwood, followed by Eucalyptus and then in Sal watersheds. Hydraulic conductivity was found to increase with moisture content. Generally, Brushwood and Eucalyptus watershed showed higher hydraulic conductivity in surface layer. In sub-surface layer Sal also revealed higher value due to low clay content. Organic matter and clay content are major determinant factors for hydraulic conductivity.